Acidentes envolvendo incompatibilidade química - Mota, Ana Luiza Capetti (Universidade Federal de São Carlos, 2023)
Chemical incompatibility can be determined from the moment that different products, in contact with each other, generate some type of danger. Dangers can be emission of gases, excessive heat, fire or even explosions. When working with chemicals, it is necessary to understand the risks and conditions related to each compound. Thus, it is essential to have knowledge about the chemical reactions, kinetics, and thermodynamics, especially the reaction enthalpy. Furthermore, the MSDS (Material Safety Data Sheet) and the chemical incompatibility table are extremely important to avoid as much as possible accidents, whether on a laboratory or industrial scale and insure adequate storage and transport for each chemical substance. This work presents the study of two accidents that occurred due to chemical incompatibility to exemplify the importance of safety data sheets in the storage, handling, and transport of chemical products. The cases chosen were the accident involving the transport of dangerous products in Rio Claro city; and the accident involving incorrect disposal of products in Pontal city.
Accidents involving chemical incompatibility
Keywords: Incompatibilidade química; Reações química; Entalpia de reação; Chemical incompatibility; Chemical reactions; Enthalpy; CIENCIAS EXATAS E DA TERRA::QUIMICA